Changes in tissue free amino acid contents, branchial Na+/K +-ATPase activity and bimodal breathing pattern in the freshwater climbing perch, Anabas testudineus (Bloch), during seawater acclimation - Chang, E.W.Y. (2014)
10.1002/jez.424